The Protective Effect of 1,25(OH)2D3 on Myocardial Function is Mediated via Sirtuin 3-Regulated Fatty Acid Metabolism - Yang, Jingxin; Zhang, Yalin; Pan, Yiming; Sun, Can; Liu, Zuwang; Liu, Ning; Fu, Yu; Li, Xiaofeng; Li, Ye; Kong, Juan (Frontiers in Cell and Developmental Biology, 2021)
Imbalance of energy substrate is a major cause of cardiac dysfunction. Vitamin D/vitamin D receptor (VD/VDR) deficiency is involved in the pathogenesis of various cardiac diseases,however, the mechanism remains unclear. The aim of this study was to investigate whether vitamin D modulated fatty acid oxidase in mitochondria via Sirtuin3 signal pathway to protect myocardium. The 1 alpha-hydroxylase-/- mice with high metabolic rate had lower myocardial contractility compared to wild type mice. Up-regulated sirtuin3 was detected in the mice treated by vitamin D3-high fat diet compared with the high fat diet mice. Sirtuin3 blocker and Sirtuin3 knockout inhibited the effect of VD/VDR on down-regulation of fatty acid oxidase in myocardial mitochondria. VD/VDR moderated fatty acid metabolism by up-regulating Sirtuin3 and lowering mitochondrial fat uptake, thereby improving myocardial function and balancing energy substance, rather than altering endocytosis and exocytosis.